2021
DOI: 10.1021/acs.jpclett.1c02809
|View full text |Cite
|
Sign up to set email alerts
|

Selective Heavy Atom Effect Forming Photosensitizing Hot Spots in Double-Stranded DNA Matrix

Abstract: Triplet exciton formation is essential for photosensitization-based photochemistry and photobiology. The heavy atom effect (HAE), in the form of either external or internal mode, is a basic mechanism for increasing the triplet exciton yield of photosensitizers. Herein, we report a new HAE mode by noncovalent cohosting of heavy atoms and photosensitizers in a double-stranded DNA (dsDNA) matrix. With dsDNA bearing several thymine (T) or cytosine (C) mismatches, heavy atoms (e.g., Hg2+ or Ag+) and dsDNA-staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Upon titration of hairpin DNA-EB with Ag + , both the fluorescence intensity and lifetime of EB experienced an initial enhancement and then quenching (Figure B and Figure S4). Such phenomenon is different from the case of normal dsDNA (no fluorescence quenching), , but in fact very similar to the previous case of Hg 2+ -selective HAE . Control investigations indicated that without the hairpin DNA, Ag + caused no significant perturbation to the EB fluorescence (Figure S5).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Upon titration of hairpin DNA-EB with Ag + , both the fluorescence intensity and lifetime of EB experienced an initial enhancement and then quenching (Figure B and Figure S4). Such phenomenon is different from the case of normal dsDNA (no fluorescence quenching), , but in fact very similar to the previous case of Hg 2+ -selective HAE . Control investigations indicated that without the hairpin DNA, Ag + caused no significant perturbation to the EB fluorescence (Figure S5).…”
Section: Resultssupporting
confidence: 70%
“…As indicated in our previous studies, here TMB oxidation could be ascribed to 1 O 2 generated from the photosensitizers (nucleic acid dyes) after binding with dsDNA (Figure S3). Besides, the difference in photosensitizer performance may be ascribed to the different binding modes of dyes with dsDNA as well as the size of the dyes, which resulted in varied distances between the photosensitizer and heavy atom (Ag + ) and thus different activation stages for the photosensitizer. For Ru­(bpy) 3 2+ , since it is already efficient in photosensitized 1 O 2 generation, the activation by Ag + may be minimal for such a photosensitizer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To prove the heavy atom and paramagnetic effects of the matrix, Ce 6@CNs with different Ln 3+ were prepared, including Y 3+ ( Z = 39, 4d 0 , diamagnetic), Gd 3+ ( Z = 64, 4f 7 , paramagnetic), and Lu 3+ ( Z = 71, 4f 14 , diamagnetic) (Figure a). Compared with the Y 3+ CNs (lower atomic number), Gd 3+ CNs exhibited a shorter fluorescence lifetime (Figure b) and stronger 1 O 2 boosting (Figure c), confirming the HAE of Gd 3+ in the matrix. , Besides, although the atomic number of Lu 3+ is larger than that of Gd 3+ , the fluorescence lifetime of Gd 3+ CNs was still lower than that of Lu 3+ CNs (Figure b), while 1 O 2 generation was higher (Figure c), thereby highlighting the potential role of the paramagnetic effect of Gd 3+ …”
Section: Resultsmentioning
confidence: 68%
“…Compared with the Y 3+ CNs (lower atomic number), Gd 3+ CNs exhibited a shorter fluorescence lifetime (Figure 2b) and stronger 1 O 2 boosting (Figure 2c), confirming the HAE of Gd 3+ in the matrix. 36,37 Besides, although the atomic number of Lu 3+ is larger than that of Gd 3+ , the fluorescence lifetime of Gd 3+ CNs was still lower than that of Lu 3+ CNs (Figure 2b), while 1 O 2 generation was higher (Figure 2c), thereby highlighting the potential role of the paramagnetic effect of Gd 3+ . 16 To better probe the inhibition of non-radiative transitions by the matrix, ThT, a famous molecular motor (with twisted intramolecular charge transfer, Figure 3a) 38 was studied here.…”
Section: ■ Results and Discussionmentioning
confidence: 97%